KLAUSULA SYARAT BATAL (EVENTS OF DEVAULT) DAN PENERAPANNYA DALAM PERJANJIAN KREDIT BANK (Faculty of Law, University of Palembang, 2022)
An event of default clause is a clause that determines an event or events which, if they occur, will give the bank the right to unilaterally terminate the credit agreement and to immediately and simultaneously collect all outstanding loans. The application of the cancellation clause is a manifestation of the freedom of initiative of bank business actors in applying the contents of credit agreements to their debtors, which generally have been standardized in writing and contain the contents of the agreement in accordance with the interests of the bank. In this case, the debtor only has to agree to the contents of the standardized agreement. Although the void condition clause is a reflection of the application of the principle of freedom of contract regulated in Article 1338 of the Civil Code, but in accordance with the principles of justice and legal certainty, the application of the void condition clause must not harm the interests of the debtor.